The Maturity Level of Education Profiling To Generate E-Learning Systems & Innovation - Gamayanto, Indra; Wibowo, Sasono (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
Knowledge and experience are two things that cannot separate; they are connected and form an inseparable unity. Knowledge has two important things: invisible knowledge based on experience and visible knowledge based on competency development. This article is a complete concept of how we can gradually improve our performance, and at each stage, there will be steps to improve this. Furthermore, this article complements previous research published, namely Development of Mentoring Management in Producing High-Quality Human Resources at University Level in Facing the Asean Economic Community (MEA) Using the Concept of Kiyosaki - Blanchard Abcd Trust Methods-Hsova. This article will discuss improving seven indicators: Strategy, Structure; Systems; Culture; Staff; Style, and Global Goals. Of course, these seven indicators are very important to discuss because, at each level, a standard will give to improve performance and systematic steps so that performance can improve stably but flexibly. The other side is the seven levels: stage 1 Uncontrolled; stage 2 The fundamentals; stage 3 The development; stage 4 Integrated; stage 5 Good University; stage 6 The Best University; stage 7 Global University. The results of this article are the maturity level of e-learning and the maturity level of the university.